2016
DOI: 10.1038/srep27754
|View full text |Cite|
|
Sign up to set email alerts
|

Ocular exposure to blue-enriched light has an asymmetric influence on neural activity and spatial attention

Abstract: Brain networks subserving alertness in humans interact with those for spatial attention orienting. We employed blue-enriched light to directly manipulate alertness in healthy volunteers. We show for the first time that prior exposure to higher, relative to lower, intensities of blue-enriched light speeds response times to left, but not right, hemifield visual stimuli, via an asymmetric effect on right-hemisphere parieto-occipital α-power. Our data give rise to the tantalising possibility of light-based interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 76 publications
(128 reference statements)
0
26
0
Order By: Relevance
“…decision outcome, reaction time, stimulus properties) have been used to investigate the relationship between brain activity and behaviour/perception (see for example Busch et al ., ; Ratcliff et al ., ; Cohen & Cavanagh, ; Pernet et al ., ; Schyns et al ., ; Cohen & Donner, ; Gross, ) unobservable in traditional analyses where trial‐by‐trial variance is eradicated through averaging of data at the single‐subject level. Typically, single‐trial neural activity is correlated with single‐trial behavioural measurements such as reaction time or accuracy (Kelly & O'Connell, ; Newman et al ., ). However, psychometric function parameter estimation requires the input of behavioural responses across multiple trials and hence cannot be defined based on single‐trial observations.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…decision outcome, reaction time, stimulus properties) have been used to investigate the relationship between brain activity and behaviour/perception (see for example Busch et al ., ; Ratcliff et al ., ; Cohen & Cavanagh, ; Pernet et al ., ; Schyns et al ., ; Cohen & Donner, ; Gross, ) unobservable in traditional analyses where trial‐by‐trial variance is eradicated through averaging of data at the single‐subject level. Typically, single‐trial neural activity is correlated with single‐trial behavioural measurements such as reaction time or accuracy (Kelly & O'Connell, ; Newman et al ., ). However, psychometric function parameter estimation requires the input of behavioural responses across multiple trials and hence cannot be defined based on single‐trial observations.…”
Section: Methodsmentioning
confidence: 97%
“…For example, pre‐stimulus oscillatory power in the alpha band (~8:14 Hz) over occipito‐parietal sites has been shown to be inversely related to the likelihood of detecting a perithreshold visual stimulus (Ergenoglu et al ., ; Van Dijk et al ., ; Busch et al ., ). Additionally, the relative lateralization of alpha power between left and right posterior brain regions has been found to predict visual field reaction time (RT) asymmetries in lateralized detection tasks, that is to predict spatial bias (Thut et al ., ; Kelly et al ., ; Newman et al ., , ). While early research mainly revealed the pre‐stimulus predictors of binary decisions in threshold detection tasks (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Transient alpha oscillations are thought to reflect a sensory gating, or prioritization, mechanism 40,41 . For example, fluctuations in the cortical alpha rhythm have been associated with visual-spatial, sensory, and objectbased attention 39,[45][46][47] , including response to blue-enriched white light 43 . Specifically, transient reduced alpha power typically reflects enhanced neuronal activity, or excitability [48][49][50] , while transient enhanced alpha power is considered a marker for cortical inhibition 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…These are thought to reflect changes in visual attention allocation and are typically observed locally as a transient decrease in alpha power, or a transient desynchronization, over the area of the brain that processes the stimulus presented [38][39][40][41][42] . Interestingly, recent evidence suggests that these more transient oscillatory changes could be modulated by prior exposure to bright blue light, likely implicating ipRGCs 43,44 . However, the transient response to light has not been investigated in blind participants retaining non-visual responses.…”
Section: The Discovery Of Intrinsically Photosensitive Retinal Ganglimentioning
confidence: 99%
“…Recently, another neuroimaging study revealed that melanopsin-based photoreception activates a cerebral network including frontal regions, classically involved in attention and oculomotor responses (Hung et al, 2017). A range of studies introduced blue-enriched white light and showed that it improves subjective alertness and performance (Viola et al, 2008), speeds response times (Newman et al, 2016) and is more effective in reducing subjective sleepiness and enhancing cognitive performance, specifically associated with tasks of sustained attention (Chellappa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%